GENERATION OF PARTICULATE AERODISPERSIONS BY MEANS OF A FUNCTIONAL GRENADE SAMPLE (Advances in Military Technology, 2022)
It followed from the results of firing tests conducted with particulate grenade models under variable weather conditions in the field that the models generated a particulate aerodispersion in a cloud effective for a short time. The tested kinds of particles produced clouds of aerodispersions of similar sizes; the cloud diameters were increasing upwardly up to the 20th second after the explosive action of spreading the charge up to the value of diameter l = ~13 m in the case of Chezarb, l = ~20 m in the case of the S244 carbon fibres, l = ~22 m in the case of brass particles, and l = ~28 m in the case of aluminium particles. Particulate systems in the cloud showed good attenuating capabilities for a short time in the whole IR range of spectrum. The tests proved that their application in the multispectral protection of military objects is desirable.